Influence Literacy Islamic Finance and Motivation for Saving Interest of Islamic Economics Study Program Students at Bank Syariah Indonesia - Sahfira Handayani; Rafiuddin Rafiuddin; Dinah Husniah (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study is motivated by the gap between students understanding of Islamic economics and their actual behavior in utilizing Islamic banking services. It aims to examine the effect of Islamic financial literacy and motivation on students saving interest in Bank Syariah Indonesia. A quantitative approach with a causal associative design was employed. Data were collected through questionnaires from 64 students of the Islamic Economics Study Program selected using simple random sampling. The data were analyzed using multiple linear regression. The findings reveal that partially, Islamic financial literacy does not significantly influence saving interest, whereas motivation has a positive and significant effect. Simultaneously, both variables significantly affect saving interest, with a coefficient of determination of 82.75%. These results indicate that motivational factors play a more dominant role than cognitive aspects in shaping students financial behavior. This study contributes to the Islamic finance literature by emphasizing the importance of integrating financial literacy and motivation in enhancing Islamic financial inclusion. Practically, the findings provide insights for Islamic banking institutions to design strategies that not only focus on improving financial knowledge but also on strengthening students motivation as potential customers.